2011
DOI: 10.1038/ncomms1278
|View full text |Cite
|
Sign up to set email alerts
|

LTD is a protein required for sorting light-harvesting chlorophyll-binding proteins to the chloroplast SRP pathway

Abstract: Higher plants require chloroplasts for essential functions in photosynthesis and other important physiological processes, such as sugar, lipid and amino-acid biosynthesis. most chloroplast proteins are nuclear-encoded proteins that are synthesized in the cytosol as precursors, and imported into chloroplasts by protein translocases in the outer and inner chloroplast envelope. The imported chloroplast proteins are then translocated into or across the thylakoid membrane by four distinct pathways. However, the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 59 publications
2
63
2
1
Order By: Relevance
“…The GST-STIC2 protein copurified efficiently with His-ALB4C in the absence of significant amounts of any other protein, providing strong evidence for a direct interaction between STIC2 and the C terminus of STIC1/ALB4 ( Figure 6A, left side). By contrast, when His-ALB4C was replaced in the assay by the His-tagged LTD stromal targeting factor (Ouyang et al, 2011), significant GST-STIC2 copurification was not detected ( Figure 6B). This demonstrated that GST-STIC2 does not associate nonspecifically with the affinity resin used to purify the His-tagged proteins, confirming that the detected copurification ( Figure 6A) reflects a genuine protein-protein interaction.…”
Section: Stic2 Interacts With the C Termini Of Alb4 And Alb3 In Vitromentioning
confidence: 97%
See 2 more Smart Citations
“…The GST-STIC2 protein copurified efficiently with His-ALB4C in the absence of significant amounts of any other protein, providing strong evidence for a direct interaction between STIC2 and the C terminus of STIC1/ALB4 ( Figure 6A, left side). By contrast, when His-ALB4C was replaced in the assay by the His-tagged LTD stromal targeting factor (Ouyang et al, 2011), significant GST-STIC2 copurification was not detected ( Figure 6B). This demonstrated that GST-STIC2 does not associate nonspecifically with the affinity resin used to purify the His-tagged proteins, confirming that the detected copurification ( Figure 6A) reflects a genuine protein-protein interaction.…”
Section: Stic2 Interacts With the C Termini Of Alb4 And Alb3 In Vitromentioning
confidence: 97%
“…Accordingly, Arabidopsis alb3 mutants display a strongly chlorotic/albino phenotype linked to defective LHCP biogenesis (Sundberg et al, 1997;Asakura et al, 2008); by contrast, those with defects affecting a second, paralogous protein called ALB4 appear relatively normal, suggesting that this factor is functionally different (Gerdes et al, 2006;Benz et al, 2009;Trösch et al, 2015). Recently, a novel component of the cpSRP pathway was identified: The LHCP targeting deficient (LTD) protein acts upstream of the cpSRP by mediating the transfer of the newly imported LHCP proteins from the TIC translocon to the cpSRP complex (Ouyang et al, 2011). Interestingly, Tic40 and Tic110 were both implicated in LTD association with the TIC, and in early recognition of LHCPs (Ouyang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins play a key role in photosynthesis and represent the most abundant transmembrane proteins in plants. After synthesis, LHCPs are translocated from the cytosol across the outer and inner envelope of chloroplasts and are subsequently routed to the cpSRP pathway by the recently identified LTD protein (10). cpSRP binds the hydrophobic LHCP to form the soluble transit complex and to deliver it to the thylakoid membrane.…”
mentioning
confidence: 99%
“…It mediates an impressive range of protein-protein interactions as follows. (a) CD2 binds to an arginine-rich motif in the C-terminal tail of cpSRP54 (14 -16), (b) the ankyrin repeats bind to the conserved L18 motif in LHCPs (17,18), (c) an interaction between cpSRP43 and LTD is involved in delivering LHCP from the envelope to cpSRP (10), and (d) cpSRP43 binds to the translocase Alb3, a process that likely plays a central role in the docking of the cpSRP⅐LHCP⅐ cpFtsY complex to Alb3 (19 -22). Furthermore, cpSRP43 acts as a chaperone for LHCPs and prevents its aggregation (23,24).…”
mentioning
confidence: 99%